2022
DOI: 10.3390/jcdd9050134
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cardio-Oncology Service in Lithuania: Prediction, Prevention, Monitoring and Treatment of Cancer Treatment-Induced Cardiotoxicity

Abstract: Background: Advances in cancer therapy have dramatically improved outcomes for cancer patients. However, cancer treatment can cause several cardiovascular (CV) complications, increasing cardiac mortality and morbidity in cancer patients and survivors. As a result, a new cardiology subspecialty—cardio-oncology (CO)—has been developed. The goals of CO are to understand the mechanism of the cardiotoxicity (CTX) of cancer therapies and invent the best monitoring and treatment strategies to improve the survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Diastolic dysfunction or deterioration may predispose the development of HF and is an early sign of cardiotoxic injury [44,45]. In a previous retrospective study of cardio-oncology patients, we showed that diastolic dysfunction worsens survival in cancer patients [46]. In the cardioprotective treatment trials, only treatment with carvedilol had a beneficial effect on diastolic function, up until now [24].…”
Section: Development Of Diastolic Dysfunctionmentioning
confidence: 94%
See 1 more Smart Citation
“…Diastolic dysfunction or deterioration may predispose the development of HF and is an early sign of cardiotoxic injury [44,45]. In a previous retrospective study of cardio-oncology patients, we showed that diastolic dysfunction worsens survival in cancer patients [46]. In the cardioprotective treatment trials, only treatment with carvedilol had a beneficial effect on diastolic function, up until now [24].…”
Section: Development Of Diastolic Dysfunctionmentioning
confidence: 94%
“…A total of 48 women with solid tumours, specifically breast cancer (46) and sarcoma (2), scheduled for anthracycline therapy and possessing an elevated heart rate (>75 BPM) at Vilnius University hospital "Santaros Clinics" between May 2019 and January 2022 were in included in the study.…”
Section: Study Participantsmentioning
confidence: 99%
“…The smooth operation of such programs requires the close collaboration of health care professionals from different specialties such as oncology, cardiology, and hematology [ 6 , 7 ]. In this regard, Čiburienė et al reported the 6-year experience of the first cardio-oncology service in Vilnius, Lithuania [ 8 ]. Among the 447 patients who were consulted, more than two thirds were female, and the median age was 64 years.…”
mentioning
confidence: 99%